Beyond competence: Paulo Freire, Jacque Rancière and the use of the 'third term' in critical pedagogy - Karolina Starego (University of Lower Silesia, 2017)
The main purpose of this paper is to call into question the use of the language of competence in critical pedagogy. I intend to show that the language of competence lies within the individualistic paradigm of education and is, in effect, useless to the critical project that aims to support social change toward a society based on community, solidarity, justice and equality. I also intend to outline a new theoretical perspective for critical pedagogy. Instead of being based on individual dispositions, this perspective focuses on process of subjectification, rooted in the "social 'we'." The individualistic framework is transcended through dialogue that is based not solely on the interpersonal relation, but also on the notion of mediation. I call this concept of pedagogy, based on theories of such authors as Jacques Rancière and Paulo Freire, "the pedagogy of the third term" or "the pedagogy of mediation."